Зміна напружень в надтвердій кераміці при вібро-абразивній обробці - Бурлаков, В. І. (Національний технічний університет "Харківський політехнічний інститут", 2019)
У статті розглянутий вплив віброабразивної обробки на зміну залишкових напружень в надтвердій кераміці. Приведені і оцінені дифрактограми поверхонь під різними кутами відображення до і після вібро-абразивної обробки. Приведена і оцінена залежність величини залишкових напружень від часу обробки, розрахунок величин залишкових напружень до і після вібро-абразивної обробки. Експериментально показано зниження залишкових напружень в надтвердій кераміці залежно від часу обробки. Надані результати стійкісних випробувань інструменту і показана можливість підвищення стійкості за рахунок управління залишковими напруженнями в інструментальному композиті.

Residual stress arises in a material during its heat treatment, transition from a liquid to a solid state, during mechanical processing, welding, etc. Residual stresses are always present in plastic, metal, and glass. The cause of the residual stresses is the heterogeneity of the deformed state of the solid due to various changes in different places of its length or volume. In some cases, it becomes necessary to reduce or completely relieve residual stresses in the product. For this, various methods can be used with respect to the part having residual stresses. Scientists tried to solve the question of changing the residual stresses in superhard ceramics in different ways. To determine the change in the magnitude of the internal stresses associated with power and thermal effects, ceramic samples were examined without treatment and after processing with different time limits, an X-ray diffraction analysis was performed using a diffractometer DRON-4-3. Due to the fact that the known methods for removing residual stresses are not effective enough for parts made of superhard ceramics, it is necessary to propose some new method of dealing with these phenomena. One of the methods for relieving internal stresses of superhard ceramics is vibration processing. There are various methods of vibration processing. For each specific case, you can choose a certain type of processing, which will provide the necessary reduction of residual stresses and deformations. The article considers the influence of vibration-abrasive processing on the change in residual stresses in superhard ceramics. The diffractograms of surfaces at various angles of reflection are presented and analyzed before and after vibro-abrasive treatment. The dependence of the value of the residual stresses on the processing time, the calculation of the values of the residual stresses before and after vibration processing are given and evaluated. Experimentally shown is a decrease in residual stresses in superhard ceramics depending on the processing time. The results of resistance tests of the tool are presented and the possibility of increasing resistance by controlling residual stresses in the tool composite is shown.
Change of stress in super-solid ceramic at vibro-abrasive processing
Keywords: дифрактограма; залишкові напруження; міцність конструкцій; бреггівські кути; diffractogram; remaining tensions; durability of constructions; bragg angles